Rare presentation of ectopic thymoma - Tanthry, Deepalakshmi; Nehla, Aisha; R., Chethana; Pannen, Devan Poothatta; Santhraya, Mahesh; Bhandary, Rukma; Pai, Vishwas (International Surgery Journal, 2021)
Thymoma is the most common tumor of the anterior mediastinum with an incidence of 0.15 cases per 100,000. Ninety percent of all thymoma occur in the anterior mediastinum, with the remainder occurring in the neck or other mediastinal areas. Ectopic cervical thymoma (ECT) is an extremely rare tumor that originates from ectopic tissue and is caused by the aberrant migration of the embryonic thymus. ECTs are often confused with thyroid or parathyroid swellings due to their anatomical positioning. Intrathyroid epithelial thymoma is a rare tumour comprising about 0.08% of all primary thyroid malignancies. It is low-grade thyroid carcinoma with squamous cell differentiation whose overall survival rate was found to be 71%. Here we presented a case of 43 year old female, came with swelling in front of the neck since many years. Ultrasound neck and fine needle aspiration cytology (FNAC) was performed. Patient underwent total thyroidectomy and specimen obtained was sent for histopathological examination. It revealed ectopic intrathyroid thymoma.